Report of the supervised teaching practice held at the Conservatório Regional de Évora - Eborae Música: attitudes and motivation in learning the piano - Lopes, Maria João Guerra (2021)
This is a report of the modules of Supervised Teaching Practice 1 and 2, part of the Master of Music Teaching´s syllabus of the Universidade de Évora; followed by an investigation section, deliberating on the theme of Attitudes and Motivation in Learning the Piano. The responsibility of the Master´s student was to analyse and comprehend the educational context of the students, their learning objectives and the teacher´s assessment criteria and instructive prospect throughout a whole school year, from September 2019 to July 2020. In this context, it is asked of the Master´s student to attend and teach six student´s instrumental lessons, and assist in other pertinent activities in a Music school. To gather as much input and data possible from the lessons, the Master´s student utilized a diary of personal observations. The focus is on the correlation between attitudes and motivation. To better understand the connection between these two elements, a thorough expound is made on the significance of each element. As a conclusive bind, motivation and attitudes, of the observed students, are intertwined to answer the following research question: Through the analysis of attitudes, how does motivation fluctuate during a piano lesson; Resumo: Título: Relatório de Prática de Ensino Supervisionada realizada no Conservatório Regional de Évora – Eborae Música: Atitudes e Motivação na Aprendizagem do Piano Este relatório é referente às disciplinas de Prática de Ensino Supervisionada 1 e 2, integradas no programa do Mestrado em Ensino de Música da Universidade de Évora; seguido de uma secção de investigação sobre o tema de Atitudes e Motivação na Aprendizagem do Piano. A responsabilidade da Mestranda era analisar e compreender o contexto educacional de alunos, os objetivos de aprendizagem, os critérios de avaliação e o planeamento do professor cooperante, ao longo de todo um ano letivo, de setembro de 2019 a julho de 2020. Neste contexto, era requerido que a Mestranda atendesse e lecionasse aulas instrumentais de seis alunos, e assistisse a outras atividades pertinentes numa escola de Música. Para obter o máximo de dados possíveis das aulas, a Mestranda utilizou um diário de observações pessoais. O foco está na ligação entre atitudes e motivação. Para entender melhor a conexão entre estes dois conceitos, uma exposição é feita sobre o significado de cada um. Para atingir conclusões, a motivação e atitudes, dos alunos observados, interligam-se para responder à seguinte questão de pesquisa: Por meio da análise das atitudes, como é que oscila a motivação durante uma aula de piano